The Recurrence Rate of Basal Cell Carcinoma with Positive Histopathological Edges and Associated Risk Factors - يوسف, عدي; سلوم, رباب (Latakia University Journal -Medical Sciences Series, 2020)
Background: The best way to approach surgically removed basal cell carcinoma with positive histopathological margins is a controversial issue. Some authors believe that the more appropriate treatment is an immediate reoperation while others prefer a periodic follow up. The rates of recurrence are variable in literature, between 10% and 67%. Objective: To define the recurrence rate of basal cell carcinoma with positive margins after surgery. Secondarily, identify morphological aspects that can suggest a more frequent tumoral recurrence. Methods: This was a retrospective and observational study made by analysis of medical records of 84 patients up to June 2018 in Tishreen University Hospital; follow up was made between June 2018 and June 2020. From 75 basal cell carcinomas surgically treated, 41 fulfilled inclusion criteria and were evaluated for two years. Recurrence rate of these tumors was analyzed in all patients and clinical characteristics such as sex, age, tumor size, tumor site, ulceration, and histological type were evaluated in order to find if they were related to more common tumoral recurrence. Results: The rate of positive margins after surgery was 65.4%. There were five cases of tumoral recurrence in the observation group and three cases in the re-excision group. Tumor size, site, histological type, ulceration and type of positive margin did not differ statistically between groups. It was not possible to consider if these factors were important in recurrence rates. Study limitations: Ideally, a prospective study with a larger sample would be more accurate. Conclusion: The treatment of choice in basal cell carcinoma with positive margins must be individualized to reduce recurrence rates.